STRUCTURAL AND OPTOELECTRONIC PROPERTIES OF ZnS NANOPARTICLES EXPOSED TO ORGANIC AND INORGANIC CAPPING AGENTS (FULafia Journal of Science and Technology, 2021)
ZnS nanoparticles capped with Sodium Carboxyl-methyl Cellulose (CMC-organic) and Tetraethylorthosilicate (TEOS-inorganic) as capping agents were synthesized by chemical co-precipitation and sol-gel technique respectively. Structural, morphological and optical studies of the synthesizes nanoparticles were carried out using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), UV-Vis spectroscopy and Fourier transforms infrared spectroscopy (FTIR). Studies of the capped ZnS nanoparticles revealed zinc blende structure.Particle sizes calculated from Williamson-Hall (W-H) analysis of Uniform Deformation Model (UDM) were (ZnS:CMC) and (ZnS:SiO ). The average strain values calculated from the model indicated that ZnS:SiO has while ZnS:CMC has All samples had smooth surfaces due topassivation of the capping agents. Optical absorption studies shows a blue shift of the absorption edge with bandgap values of and for ZnS:CMC and ZnS:SiO which are higher than the bulk value of ZnS nanoparticles due to quantum confinement effect. The vibrational modes associated with OH-stretching at and the carboxylic group –COOH at confirms the presence of capping agent from the Fourier transform infrared spectroscopy measurement.
Keywords: ZnS; Capping agents; Chemical route; Sol-gel; Nanoparticle sizes; Strain and Optoelectronic